Conductance and Dielectric Anisotropy Properties of 4'-Hexyl-4-biphenylcarbonitrile and 4'-Octyloxy-4-biphenylcarbonitrile Liquid Crystals and Their Composite - Ozgan, Sukru; Yazici, Mustafa; Ates, Kemal (Asian Journal of Chemistry, 2011)
The absorbance, conduction and dielectric properties of 4'-hexyl-4-biphenylcarbonitrile, 4'- octyloxy-4-biphenylcarbonitrile and their composite liquid crystals have been investigated. The absorbancies of samples have been studied using the ultraviolet visible spectrometry. The conduction and dielectric measurements of liquid crystals and their composite have been prepared in the frequency range of 0 kHz to 1 MHz at the room temperature. The difference of birefringence index is negative after a certain frequency when increased frequency. This frequency is 780 kHz for 4'-hexyl-4-biphenylcarbonitrile liquid crystal. The splay elastic constant K11 values decreases with increasing frequency. The dielectric and birefringence index difference of the 4'-hexyl-4- biphenylcarbonitrile/4'-octyloxy-4-biphenylcarbonitrile composite decreases with mixing of 4'- octyloxy-4-biphenylcarbonitrile to 4'-hexyl-4-biphenylcarbonitrile. The capacitance is large for low voltage, small for high voltage and it decreases with increasing frequency. The conductance is large for high voltage, small for low voltage and it increases with increasing frequency.